Our psychiatric future and the (bio)politics of Mental Health: dialogues with Nikolas Rose - Sérgio Resende Carvalho; Henrique Sater de Andrade; Luana Marçon; Fabrício Donizete da Costa; Silvio Yasui (Faculdade de Medicina de Botucatu (Unesp), 2020)
Here we present the last of a series of four interviews with English sociologist Nikolas Rose. We explore central aspects of the recently published work entitled "Our Psychiatric Future: politics of Mental Health policies", which has as background issues and problems that we consider absolutely relevant for facing the complex and difficult challenges posed to the implementation of Brazilian Public Health system and to the reform of Mental Health in our country. In this interview, we seek to discuss with the author: psychiatry as a (bio)politics; the 'epidemics' of mental disorders'; the role and consequences of psychiatric diagnostic practice in defining what is defined as mental disorder or illness; the use and abuse of psychiatric drugs in the contemporary; strengths and weaknesses of discursive psychiatric practices in 'developed' countries; limits and possibilities of users' participation in Mental Health.